"Advocating Every Single Day" so as Not to be Forgotten: Factors Supporting Resiliency in Adult Day Service Centers Amidst COVID-19-Related Closures. Issue 3 (3rd April 2021) - Sadarangani, Tina; Zhong, Jie; Vora, Paayal; Missaelides, Lydia
ABSTRACT: Adult day centers (ADCs) are nonresidential settings that support the health and social needs of vulnerable older adults. Due to ADCs' congregate nature and participants' compromised health status, many ADCs have been forced to close during the COVID-19 pandemic. It is unknown how closures have impacted service delivery at ADCs. Guided by the Resiliency Activation Framework, we (a) identified consequences resulting from closures of ADCs during the COVID-19 pandemic and (b) described factors that have enabled the ADC community to remain resilient in the wake of challenges brought on by the pandemic. We conducted 2 focus groups in California ( n = 12), and individual interviews with ADC staff members ( n = 8) in 7 other states. The results of a directed content analysis revealed perceived declines in physical, cognitive, and mental health of ADC users and increased caregiver strain. Access to human, social, economic, and political capital were essential for supporting ADCs in buffering the impacts of the pandemic on the older adults they serve but were not consistently available. Research is urgently needed that quantifies the impacts of the pandemic on ADC users and their caregivers to inform policy and advocacy efforts in the wake of the pandemic.